Determinan Keputusan Pembelian Micellar Water pada Generasi Z: Peran Kualitas Produk, Word of Mouth, dan Citra Merek - Permatasari, Aldila Kurnia Dian; Lestari, Diah Yuli (Graha Mitra Edukasi, 2026)
The purpose of this study is to examine the effects of product quality, word of mouth, and brand image on the purchase decision of Garnier Micellar Water among Generation Z in Tangerang City. This study employed a quantitative approach using primary data collected through an online questionnaire. A total of 100 respondents were selected using a non-probability sampling method with a purposive sampling technique. The data analysis procedures included validity testing, reliability testing, classical assumption tests consisting of normality, multicollinearity, and heteroscedasticity tests, multiple linear regression analysis, the F-test (simultaneous), the t-test (partial), and the coefficient of determination (R²). The results indicate that product quality, word of mouth, and brand image have a positive and significant effect on the purchase decision of Garnier Micellar Water. Partially, product quality (p = 0.006), word of mouth (p = 0.045), and brand image (p = 0.016) were found to have significant effects on purchase decisions (p < 0.05). Simultaneously, product quality, word of mouth, and brand image also have a significant effect on the purchase decision of Garnier Micellar Water (F = 110.433; p = 0.000). This study contributes to the marketing literature by providing empirical evidence on the role of product quality, word of mouth, and brand image as determinants of purchase decisions. Furthermore, the findings offer practical insights for companies in formulating more effective marketing strategies to enhance consumers' purchase decisions, particularly among Generation Z.